2015
DOI: 10.1007/s00707-015-1311-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelastic instability of functionally graded materials in frictionless contact

Abstract: This paper investigates the static thermoelastic instability between a functionally graded material (FGM) half-plane and a homogeneous half-plane under the plane strain state using the perturbation method. Two frictionless half-planes are pressed together by a uniform pressure and transmit a uniform heat flux at their interface where a pressure-dependent thermal contact resistance is taken into account. The material properties of the FGMs are assumed to be of an exponential form. The characteristic equation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Their results showed that controlling a material property gradient in FGMs could lead to a significant improvement in the resistance to the contact deformation and damage [34][35][36][37][38][39]. In the past few years, the frictionally-excited TEI and static TEI of FGMs were investigated by Jang and his co-authors [40,41] and Ke and his co-authors [2,42,43], respectively. Specially, Liu et al [44] analyzed the dynamic instability of an elastic solid sliding against a functionally graded material coated half-plane without frictional heat.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 4 more Smart Citations
“…Their results showed that controlling a material property gradient in FGMs could lead to a significant improvement in the resistance to the contact deformation and damage [34][35][36][37][38][39]. In the past few years, the frictionally-excited TEI and static TEI of FGMs were investigated by Jang and his co-authors [40,41] and Ke and his co-authors [2,42,43], respectively. Specially, Liu et al [44] analyzed the dynamic instability of an elastic solid sliding against a functionally graded material coated half-plane without frictional heat.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Compared with our previous papers [2,42,43,45] on the TEI of FGMs, the new aspects of this paper are: (1) The main concern of these papers was placed on the static TEI of FGMs, which was induced only by the thermal contact resistance. In this paper, we discuss the coupled effect of the frictional heating and thermal contact resistance on the TEI of FGMs.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations